Developing pre-service teachers' evidence-based argumentation skills on socio-scientific issues - Iordanou, Kalypso; Constantinou, C. P. (Learning and Instruction, 2014)
We report on a study of the effect of meta-level awareness on the use of evidence in discourse. The participants were 66 pre-service teachers who were engaged in a dialogic activity. Meta-level awareness regarding the use of evidence in discourse was heightened by having same-side peers collaborating in arguing on the computer against successive pairs of peers on the opposing side of an issue on the topic of Climate Change and by engaging in explicit reflective activities on the use of evidence. Participants showed significant advances both in their skill of producing evidence-based arguments and counterarguments and regarding the accuracy of the evidence used. Advances were also observed at the meta-level, reflecting at least implicit understanding that using evidence is an important goal of argumentation. Another group of pre-service teachers, who studied about the role of evidence in science in the context of regular curriculum and served as a control condition, did not exhibit comparable advances in the use of evidence in argumentation. Educational implications are discussed.